Pengaruh Akuntansi Konservatif, Leverage, Growth Opportunity, Firm Size, dan Persistensi Laba Terhadap Earnings Response Coefficient - Febriyanti, Amanda; Kusumawati, Eny (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The Earnings Response Coefficient (ERC) reflects how strongly a company's reported earnings impact its stock price. This study investigates the influence of conservative accounting, leverage, growth opportunities, firm size, and earnings persistence on ERC among firms in the primary consumer goods sector listed on the Indonesia Stock Exchange between 2021 and 2023. Using purposive sampling, 162 companies met the criteria for analysis. Multiple linear regression was employed to examine the data. The findings reveal that conservative accounting and leverage significantly affect ERC, indicating that investors respond more to earnings information when companies apply prudent accounting practices or carry notable debt levels. In contrast, growth opportunities, firm size, and earnings persistence show no significant impact on ERC. These insights can help companies enhance financial transparency and guide investors and regulators in evaluating the market’s reaction to financial reports.